Command in Twenty-First Century Counterinsurgency - Warren Anthony Chin (Revista Científica General José María Córdova)
This article examines the challenges of command in counterinsurgency through the British experience in Basra, Iraq (2006–2007). It argues that command is shaped less by individual leaders than by structural and temporal constraints inherent in the strategic culture of liberal states. Using a qualitative case study and the conceptual lenses of “wartime” and “high modern utopianism,” the paper analyses command during Operation Sinbad. The analysis finds that a temporal paradox—pitting the long-term requirements of insurgency against short-term political timelines—fundamentally undermined the mission. This contradiction led to resource shortfalls and institutional fragmentation that crippled the “comprehensive approach”. The paper concludes that tactical actions, however skilful, cannot overcome the institutional pathologies defining how Western states prosecute such wars.